Šiuolaikinė lietuvių istoriografija: „tautos" samprata ir istorijos metodologija - Potašenko, Grigorijus (Lietuvos istorijos studijos, 1997)
The conception of „nation" as any conception is an instrument. The conception of nation is implicated in the methodology of history. What links exist between this conception and the methodology of history? What are the differences between the conceptions of nation of those historians whose methodologies of history are various? In this article, the methodological positions of five contemporary Lithuanian historians are under analysis. The conceptions of nation of Rimantas Vebra, Egidijus Aleksandravičius, and Antanas Kulakauskas are typologically similar and are described as being in ethnocultural and social criteria. The looks for the methodology of history of these historians mean opposition to attachment great importance of economical factors in the Lithuanian Marxist methodology of history, and to the conception of humanistic history. The critical Marxist, Leonas Mulevičius, describes the conception of nation more according to economical criteria. Vincas Trumpa disposes to the study of consciousness, research of the „life of soul of man" and describes „the nation" according to historical, self-conscious criteria. The methodology of historians of Lithuania not only means changes of a world outlook and ideology, but it also marks off a new phase (and different directions) in the history of science.